Early Erythropoietin Therapy Attenuates Remodeling and Preserves Function of Left Ventricle in Porcine Myocardial Infarction. (1st March 2011) - Chua, Sarah; Leu, Steve; Lin, Yu-Chun; Sheu, Jiunn-Jye; Sun, Cheuk-Kwan; Chung, Sheng-Ying; Chai, Han-Tan; Lee, Fan-Yen; Kao, Ying-Hsien; Wu, Chiung-Jen; Chang, Li-Teh; Ko, Sheung-Fat; et al.
Abstract : Erythropoietin (EPO) has been shown to have anti-inflammatory, antiapoptotic, and proangiogenic effects. This study investigated whether early EPO treatment effectively preserves left ventricular (LV) function in porcine acute myocardial infarction (AMI). Eighteen male mini-pigs divided into groups 1 (sham), 2 (AMI), and 3 (AMI with 2 consecutive EPO doses [7500 IU per animal each time] at 30 minutes and 24 hours after AMI induction) underwent echocardiography before and 14 days after AMI induction through left anterior descending artery (LAD) ligation with myocardium harvested for analysis. Larger infarcted areas (IA) were noted in group 2 than in group 3. In both IA and peri-IA, percentage of apoptotic nuclei and CD40-positive cells, messenger RNA expressions of IL-8, matrix metalloproteinase-9, caspase-3, and Bcl-2 associated x protein were highest, whereas proliferator-activated receptor-γ coactivator-1α, endothelial nitric oxide synthase and Bcl-2 were lowest in group 2. Oxidative stress and cytosolic cytochrome c in IA were increased ( P < 0.001), whereas protein expression of connexin43, cytochrome c, and protein kinase C-ε in mitochondria were reduced in group 2 than in other groups ( P < 0.045). The fibrosis in IA was notably decreased in group 3 compared with that in group 2. The number of small arterioles and capillary density in IA was highest in group 3, whereas LV performance was lowest in group 2 ( P < 0.045). In conclusion, the results demonstrated that early EPO administration in a porcine AMI model effectively limits infarct size, attenuates LV remodeling, and preserves LV function.